Moving urban water infrastructure asset management from science into practice. Issue 2 (17th February 2016) - Leitão, João P.; Coelho, Sérgio T.; Alegre, Helena; Cardoso, Maria A.; Silva, Maria S.; Ramalho, Pedro; Ribeiro, Rita; Covas, Dídia; Poças, Ana; Vitorino, Diogo; Almeida, Maria C.; Carriço, Nelson
Abstract : iGPI, the National Initiative for Infrastructure Asset Management is a Portuguese collaborative project led by LNEC (National Civil Engineering Laboratory, Portugal) through which 19 water utilities develop their own infrastructure asset management (IAM) systems and plans in a joint training and capacitation programme. Technical assistance to the participating utilities is ensured by LNEC, IST (Technical University of Lisbon) and Addition, a software development company. The water utilities get collective as well as one-on-one support and specific training. They benefit from networking with the other utilities in a common and simultaneous process, with similar difficulties and challenges, leading to an effective sharing of solutions. The developed products, including training materials, templates and guidelines for developing strategic and tactical IAM plans, are available to the general public. This project has greatly contributed to the establishment of reference methodologies and standards for IAM planning, in a range of utilities of widely diverse size and context, effectively defining an accepted best practice. This paper discusses the project's format and its advantages, and goes on to describe the main outcomes, including selected cases and final products.